The Role of Social Media Marketing Activities in Destination Image Formation - ABEID ALLAH Fatima; CHAKOUR Samira (Journal of North African Economies, 2025)
The COVID-19 pandemic has had significant impact on international tourism, prompting tourism organizations to focus on local tourism to alleviate their losses. Social media platforms are one of the strategies used by these organizations to promote their offerings for local tourists. This paper endeavors to provide a more thorough understanding for the role of social media marketing activities in destination image formation. The study used an online self-administered questionnaire to collect data from 172 individuals who follow social media accounts promoting Bejaia town as a tourist destination. The research model was tested using a variance-based structural equation modeling (PLS-SEM) approach, while the data were analyzed with SmartPLS4. The research reveals that affective image has a considerable influence on conative image, while cognitive image has an impact on both affective and conative image. However, only customization was found to have a significant impact on cognitive image among the SMMAs dimensions evaluated.